2004
DOI: 10.1007/bf03350906
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative evaluation of parathyroid lesions in patients with concomitant thyroid disease: role of high resolution ultrasonography and dual phase technetium 99m sestamibi scintigraphy

Abstract: The aim of this study was to evaluate the sensitivity and usefulness of high resolution ultrasonography (US) and dual phase technetium-99m sestamibi (Tc-MIBI) scintigraphy in the preoperative localization of parathyroid lesions in patients with or without thyroid disease and to define the impact of the presence of thyroid disease on these methods. Preoperative US and scintigraphy were performed on 52 patients with primary hyperparathyroidism. Age, gender, preoperative parathyroid hormone level, serum calcium l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 27 publications
3
55
1
9
Order By: Relevance
“…The results of the statistical analysis of data from group C confirm the findings of numerous other studies [29][30][31][32], that is that preoperative use of ultrasound and scintigraphy in parallel improves accuracy in the detection and localization of single pathological parathyroid glands In fact, the use of both methods was associated with higher diagnostic sensitivity (87 %) than use of ultrasound (71 %) or scintigraphy (73 %) alone. We nonetheless feel that, as reported in previous studies, the inferior sensitivity of ultrasonography observed in Group C is due to the absence of dedicated physician sonographers and/or to the relative lack of experience of some of the examiners.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the statistical analysis of data from group C confirm the findings of numerous other studies [29][30][31][32], that is that preoperative use of ultrasound and scintigraphy in parallel improves accuracy in the detection and localization of single pathological parathyroid glands In fact, the use of both methods was associated with higher diagnostic sensitivity (87 %) than use of ultrasound (71 %) or scintigraphy (73 %) alone. We nonetheless feel that, as reported in previous studies, the inferior sensitivity of ultrasonography observed in Group C is due to the absence of dedicated physician sonographers and/or to the relative lack of experience of some of the examiners.…”
Section: Discussionsupporting
confidence: 83%
“…The reported sensitivity of sestamibi scintigraphy is similar to sonography, ranging between 73-93% with a positive predictive value of 89-97%. 52,60,61,63,64,[66][67][68] The sensitivity and positive predictive value of scintigraphy also decrease in the presence of multigland parathyroid disease and multinodular thyroid disease. Other imaging modalities such as MRI and CT have also been used.…”
Section: 132342-65mentioning
confidence: 89%
“…It is effective in identifying parathyroid disease although its reported sensitivity varies widely from 42% to 96%. 4,10,[15][16][17][18][19][20][21] Ultrasonography is well recognised as being 'operator dependent' and the accuracy of parathyroid ultrasonography has been shown to be affected by operator experience. 4,5,17 A dedicated, experienced parathyroid ultrasonographer optimises preoperative parathyroid localisation whereas multiple ultrasonographers of varying experience performing less parathyroid ultrasonography may compromise parathyroid localisation.…”
Section: Discussionmentioning
confidence: 99%
“…21 One unexpected finding was a trend towards inferior parathyroid glands being easier to identify than superior glands, perhaps due to their more superficial location in the neck and the optimisation of neck extension under anaesthesia.…”
Section: Aspinall Nicholson Bliss Lennardmentioning
confidence: 99%